Sleep-disordered breathing, impaired cardiac adrenergic innervation and prognosis in heart failure. Issue 22 (23rd June 2016) - Scala, Oriana; Paolillo, Stefania; Formisano, Roberto; Pellegrino, Teresa; Rengo, Giuseppe; Gargiulo, Paola; De Michele, Fausto; Starace, Antonio; Rapacciuolo, Antonio; Parisi, Valentina; Prastaro, Maria; Piscopo, Valentina; et al.
Abstract : Objective: Unfavourable effects of sleep-disordered breathing (SDB) in heart failure (HF) are mainly mediated by impaired sympathetic activity. Few data are available on SDB and cardiac adrenergic impairment evaluated at myocardial level. The aim of the study was to assess the relationship between SDB, cardiac sympathetic innervation assessed by 123 I-metaiodobenzylguanidine ( 123 I-MIBG) imaging and prognosis in HF. Methods: Observational, prospective study enrolling patients with HF and reduced systolic function. Patients underwent nocturnal cardiorespiratory monitoring to assess SDB presence by apnoea/hypopnoea index (AHI), and 123 I-MIBG imaging to calculate heart-to-mediastinum (H/M) ratios and washout rate. Patients were prospectively followed for 29±18 months for the combined endpoint of cardiovascular death and HF hospitalisation. Results: Ninety-four patients (66.1±9.8 years; left ventricular ejection fraction 32±7%) were enrolled; 72 (77%) showed SDB and, compared with non-SDB, significantly reduced early (1.67±0.22 vs 1.77±0.13; p=0.019) and late H/M ratios (1.50±0.22 vs 1.61±0.23; p=0.038). Dividing patients into two groups according to SDB severity, patients with a moderate–severe disturbance (AHI >15; n=43) showed significantly worse survival for the composite study outcome (log-rank test, p=0.001) with respect to patients with mild or no disorder (AHI ≤15; n=51). Adding SDB variables to the already known prognostic role of 123 I-MIBG imaging, we observed a worse survival in patients with both SDB and H/M impairment. Conclusions: Patients with systolic HF and SDB show more impaired cardiac adrenergic innervation assessed by 123 I-MIBG imaging, and more adverse prognosis compared with HF patients without SDB.